A Review on Staphylococcus Pseudintermedius - Sudha, A. Kavya (International Journal of Scientific Research and Management (IJSRM), 2025)
Staphylococcus pseudintermedius is a form of bacteria commonly discovered in animals' pores skin and mucous membranes. It is normally harmless. It is a coagulase tremendous, normal inside the dog population, where it can opportunistically cause several infections, such as pores and skin and gentle tissue infections, urinary tract infections, and bacteremia. Its capability to shape biofilms and convey virulence elements, including pollution and enzymes, contributes to its pathogenic capacity. The emergence of methicillin-resistant S. Pseudintermedius (MRSP) has similarly complex treatment of infections, highlighting the want for persevered studies into the epidemiology, pathogenesis, and therapeutic techniques for this important veterinary pathogen.